Synthesis of Narrow Polydispersity Block Copolymers of PtBA-PS by Novel RAFT Polymerization Technique - M. Arcana; K. Nagesh; Ramakrisnan Rama (Journal of Engineering and Technological Sciences, 2004)
The synthesis of narrow disperse polystyrene (PS) and poly-t-butylacrylate (PtBA) was carried out by copolymerization using benzyldithiobenzoate as the chain transfer agent (CTA). Benzyl dithiobenzoate as a reversible addition-fragmentation chain transfer (RAFT) agent has high transfer coefficient in polymerization of styrene to produce PS with higher molecular weight than that of calculated, in contrary with polymerization of t-butylacrylate to produce PtBA. These results were attributed to instability the benzyl dithiobenzoate as RAFT agent under the reaction conditions. PS as a macro-CTA is not active for t-butylacrylate polymerization due to low transfer coefficient. On the other hand PtBA as the macro-CTA is active to polymerize styrene to produce PtBA-PS block copolymer with high transfer coefficient if PtBA as macro-CTA have narrow polydispersity. The RAFT agent appears to degrade over a period of time when it is left at room temperature, which was evident from the results of PtBA.